2017
DOI: 10.1007/s11916-017-0606-z
|View full text |Cite
|
Sign up to set email alerts
|

Medication Overuse in Chronic Pain

Abstract: Although antidepressants and membrane stabilization agents contribute to the crucial components for neuromodulation, opioids were frequently designated as a rescue remedy in chronic pain since adjunct analgesics usually do not provide instantaneous relief. The updated CDC guideline for prescribing opioids has gained widespread attention via media exposure. Both patients and prescribers are alerted to respond to the opioid epidemic and numerous complications. However, there has been overuse of non-opioid adjunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 53 publications
0
24
0
1
Order By: Relevance
“…The addition of intravenous sedation increases the complexity of appropriate monitoring, and may diminish cost savings [1, 3]. There are also substantial public health concerns about oral opioid and benzodiazepine overuse in the United States [17-20]. Nonpharmacologic adjuncts would therefore be useful in enhancing patient comfort without the cost and safety concerns associated with intravenous sedation and oral pain control and anxiolytics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of intravenous sedation increases the complexity of appropriate monitoring, and may diminish cost savings [1, 3]. There are also substantial public health concerns about oral opioid and benzodiazepine overuse in the United States [17-20]. Nonpharmacologic adjuncts would therefore be useful in enhancing patient comfort without the cost and safety concerns associated with intravenous sedation and oral pain control and anxiolytics.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that many rhinologic procedures can be tolerated in the office setting with just local anesthesia in combination with nonpharmacologic adjuncts. This has important implications for avoiding the use of oral opioids and benzodiazepines during a national epidemic of the abuse of these drugs [17-20]. Intravenous sedation is also likely unnecessary and eliminates the need for additional equipment and safety monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested in our editorial on the perioperative use of opioid analgesics more than a decade ago, encouraging more liberal use of opioid analgesics in acute and chronic pain management (as well as in hospice care) has directly contributed to the current opioid abuse problem [2]. Changing the opioid prescribing practices after elective surgery and in emergency departments which have contributed to persistent opioid use and abuse is an easy first step in controlling the widespread abuse of opioid medication [31,38,39]. Finally, utilizing an integrative (inter-disciplinary) approach to pain management [41,42] involving more aggressive use of non-opioid analgesics, physical-and psychological-based therapies, as well as novel innovative non-pharmacologic complementary and 'alternative' therapies (e.g.…”
mentioning
confidence: 99%
“…Of importance, Barnett et al [38] reported in a recent issue of the New England Journal of Medicine that long-term opioid use was increased in previously opioid-naive patients who received treatment in an emergency department from high (vs. low)-intensity opioid prescribers. Altering the prescribing habits of physicians and their surrogates to emphasize the role of non-opioid analgesic drugs and innovative non-pharmacologic approaches for treating acute and chronic pain would be an important first step in controlling the current opioid crisis [28,39].…”
mentioning
confidence: 99%